The moderation effect of entrepreneurial resilience on the relationship between financial literacy and sustainable performance - Alshebami, Ali Saleh; Murad, Majid (Frontiers in Psychology, 2022)
The study intends to examine the role of financial literacy in sustainable development in Saudi Arabia, with the moderating effect of entrepreneurial resilience. The data for this study was gathered from 203 different sector entrepreneurs in Saudi Arabia using a convenience sampling technique. The hypothesis was tested through the use of Smart-PLS software 3.3.9 version square structural equation modeling technique. The findings show that financial literacy has a significant and positive impact on long-term performance. In the meantime, research indicates that entrepreneurial resilience has a significant and positive effect on long-term performance. Furthermore, the findings show that entrepreneurial resilience moderates the relationship between financial literacy and long-term performance in Saudi Arabia. Furthermore, this research article addressed the practical and theoretical implications of the study.